Plant microbiology (Garland Science / BIOS Scientific Publishers, 2004)
This title, written by experts in the field, provides a comprehensive source of information on DNA sequencing and mapping. The newest technology and procedures in areas such as radiation hybrid mapping, FISH and specialized sequencing techniques are covered. The book also describes how transgene expression is controlled in plants and how advanced information strategies can be used to manipulate and modify the plant genome. The final chapter provides an overview of all the applications of plant transformation in agriculture, medicine and industry.